THE IMPACT OF OVERUSING SMARTPHONES ON SOCIAL INTERACTION PATTERNS ON STUDENTS AT FACULTY OF SOCIAL SCIENCE UNIVERSITAS NEGERI PADANG - Ikhwan Ikhwan; Mutiara Karlina (Jurnal Ranah Komunikasi, 2023)
This research is motivated by the high level of importance of using smartphones for FIS UNP students, which reaches more than 90% with a range of smartphone usage per hour reaching 10 to 13 hours a day. This study aims to determine the impact of excessive smartphone use on social interaction patterns of FIS UNP students who are categorized as sufferers of nomophobia. This study uses a descriptive qualitative approach with purposive sampling technique of collecting informants. Data collection techniques used in this study consisted of observation, interviews, and documentation. Then the data analysis technique refers to the thinking of Miles and Huberman which consists of data reduction, data presentation, and drawing conclusions. To obtain data with a high level of validity, the data triangulation method was used. The results of this study indicate that the impact of excessive smartphone use on students' social interaction patterns can be positive and negative. The positive impact of excessive use of smartphones on students' social interaction patterns is the increase in the circle of friends, the presence of smartphones makes the spectrum of student communication wider, and up-to-date with the latest information. The negative impact of excessive use of smartphones on students' social interaction patterns is the decline in the quality of communication and face-to-face interactions directly, not focusing when studying and communicating intensely, and tending to be happier with their world.